2008
DOI: 10.1073/pnas.0706764105
|View full text |Cite
|
Sign up to set email alerts
|

Knockin mice expressing a chimeric p53 protein reveal mechanistic differences in how p53 triggers apoptosis and senescence

Abstract: The contribution of transcriptional activation to the p53 effector functions critical for tumor suppression, apoptosis and cellular senescence, remains unclear because of p53's ability to regulate diverse cellular processes in a transactivation-independent manner. Dissociating the importance of transactivation from other p53 functions, including regulating transcriptional repression, DNA replication, homologous recombination, centrosome duplication, and mitochondrial function, has been difficult because of ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 38 publications
0
20
0
1
Order By: Relevance
“…Tumors were not observed in the ⌬40p53 mice 9 and not reported for another N-terminally truncated p53 mouse, 28 but mice containing small deletions or point mutations in the N-terminus of p53 are tumor prone, [29][30][31] predominantly developing B-cell tumors. In these cases, the tumors appeared much later than in ⌬122p53 mice and are the result of impaired p53 function.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors were not observed in the ⌬40p53 mice 9 and not reported for another N-terminally truncated p53 mouse, 28 but mice containing small deletions or point mutations in the N-terminus of p53 are tumor prone, [29][30][31] predominantly developing B-cell tumors. In these cases, the tumors appeared much later than in ⌬122p53 mice and are the result of impaired p53 function.…”
Section: Discussionmentioning
confidence: 99%
“…Obligatory loss of transactivation function in senescence bypass-selected p53 mutants would support the findings from a recent study in knock-in mice harboring a chimeric p53 protein lacking motifs for nontransactivation-related functions. This elegant report demonstrated that p53-induced senescence of primary MEFs is dependent on the transactivation properties of p53 (52).…”
Section: Discussionmentioning
confidence: 99%
“…Cite this article as Cold Spring Harb Perspect Biol 2009;00:a001883 of transactivation ( p53VP16), but lacking domains involved in transactivation-independent functions (i.e., transcriptional repression) (Johnson et al 2008). p53VP16 was able to robustly transactivate p53 targets involved both in apoptosis and senescence.…”
Section: Tumor Suppressive Functions Of P53mentioning
confidence: 99%